Effect of Situational Factors and Product on Consumer Buying Decision In Hypermart at Manado City - Nova Christian Mamuaya (DeReMa (Development Research of Management): Jurnal Manajemen, 2016)
This research aims at (1) understanding and analyzing the effect of situational and non situational (produc) factors, simultaneously or partially, on the consumer buying decision in hypermart at Manado City, (2) understanding and analyzing factor with dominant effect on consumer buying decision in hypermart at Manado City.The observed situational and non situational (product) factors through Belk Theory. Sampling has been developed through accidental sampling, resulting in 60 respondents. Data  have  been  collected  by main instrument of questionnaire, 5-point Likert Scale to measure the respondents’ answer, data analysis using multiple linier regression.Results of research indicate that situational factor and product have significant effect simultaneously or partially on consumer buying decisions in hypermart at Manado City and product assortment has dominant effect on consumer buying decision in hypermart at Manado City.